Structure of the sucrose synthase gene on chromosome 9 of Zea mays L - Werr, W. (1985)
The structure of the shrunken gene of Zea mays encoding sucrose synthase (EC 2.4.1.13) was determined by (i) sequencing the transcription unit and ˜1.2 kb of 5' -upstream sequences from a genomic clone, (ii) by sequencing a nearly full length cDNA clone and (iii) by determining the transcription start site by a combination of primer extension experiments with synthetic oligodeoxynucleotide primers and S1 mapping. The sucrose synthase gene is 5.4 kb long, of which 2746 bp are found in the mature mRNA. The gene is interrupted by 15 introns. The first two introns are ˜1 kb and ˜0.5 kb in length, respectively, while the other introns are much smaller. A TATA box is located 30 bp upstream from the transcription start site. Approximately 610 bp upstream of the transcription start site a direct repeat of 16 nucleotides, separated by a 4-fold repetition of the sequence GGTGG is detected. The 16-bp sequence has similarities to a sequence repeat found between two promoters of a maize zein gene also expressed in the endosperm tissue. The transposable element Ds in the mutant sh-m5933 and sh-m6233 alleles is inserted in the seventh and first intron, respectively. The genomic and cDNA clones were obtained from different maize lines. This allows the determination of polymorphic sites which are frequent in 3rd codon position and absent in 1st and 2nd codon positions. In addition, the 3' -untranslated sequence shows two duplications that may have arisen by the insertion and subsequent excision of transposable elements.